Unravelling the Role of Serum Kallistatin on Cardiorenal Outcomes in Kidney Transplant Survivors - Krzysztof Batko; Anna Sączek; Małgorzata Banaszkiewicz; Jolanta Małyszko; Ewa Koc-Żórawska; Marcin Żórawski; Karolina Niezabitowska; Katarzyna Siek; Andrzej Kraśniak; Marcin Krzanowski; Katarzyna Krzanowska (Kidney & Blood Pressure Research)
Introduction: Kallistatin, a serine protease inhibitor, has been implicated in cardiovascular and renal protection. This study investigates its association with clinical characteristics and outcomes in long-term kidney transplant recipients (KTRs). Methods: In this longitudinal observational cohort study, we enrolled 101 KTRs between September 2016 and October 2017. The median (interquartile range) time post-transplant was 52 (36–97) months, and the follow-up time was 83 (41–85) months. All patients had documented graft function of ≥24 months and no record of acute rejection or active or chronic infection at presentation. Serum kallistatin and high-sensitivity interleukin-6 were measured at baseline using commercially available enzyme-linked immunosorbent assays. A control group of 32 healthy volunteers was also recruited. Results: Higher serum kallistatin levels were observed in KTRs compared to healthy controls (15.9 vs. 13.8 µg/mL; p = 0.007). Concentrations were lower in diabetic versus non-diabetic KTR (14.8 vs. 16.4 µg/mL; p = 0.021). A significant interaction between diabetic status and body mass index indicated a positive association with kallistatin levels only in diabetic KTRs (p = 0.046). Linear mixed models assessing estimated glomerular filtration rate (eGFR) change over time showed improved fit after kallistatin was included in a base model with age, sex, and baseline eGFR (p = 0.024). Cox regression showed that higher kallistatin levels were associated with an increased risk of graft loss (HR: 1.120; p = 0.049), but also remained independent of time after transplantation (HR: 1.147; p = 0.030). No association was observed for all-cause mortality. The best performance was estimated for kallistatin models adjusting for time post-transplant (c-index 0.779) and diabetic status (c-index 0.707). Conclusion: This study highlights the complex interactions between kallistatin, renal function, and cardiometabolic status in stable, long-term KTRs. Higher kallistatin levels are associated with an increased risk of graft loss in non-diabetic patients while showing a protective effect in diabetic patients. These findings support integrated management of cardio-reno-metabolic health in KTRs.